Karapandzic flap as most adequate surgical approach for squamous cell carcinoma of the lower lip (Dermatology Reports, 2022)
We present an 80-year-old patient with a fast-growing lesion on the lower lip, lasting for no longer than one year. The clinical examination revealed the presence of endophytically growing tumour formation along almost the entire length of the lower lip, associated with spontaneous bleeding as well as severe pain on palpation [...].